Hubungan Rasio APO-B/APOA-I dengan Index Massa Tubuh - Megawati, Megawati; Kurniawan, Liong Boy; Bahrun, Uleng (Jurnal Kesehatan, 2022)
Body Mass Index (BMI) is a simple way to monitor weight. Overweight as a result of excessive body fat accumulation which is characterized by a decrease in HDL (High-Density Lipoprotein), namely the atherogenic side represented by levels of Apolipoprotein AI (ApoA-I), increased triglycerides (TG), VLDL (Very Low-Density Lipoprotein). ), LDL (Low-Density Lipoprotein), and Total Cholesterol which is the anti-atherogenic side represented by the levels of Apolipoprotein B (Apo-B). If we measure both Apo-B and ApoA-I and express them as the Apo-B/ApoA-I ratio, we get a strong marker of cardiovascular risk. By combining the two markers in the ratio, we get synergies and increase predictive power. This study aims to analyze the levels of Apo-B, ApoA-I, and the ratio of Apo-B/ApoA-I to BMI. An experimental study with a cross-sectional design using 72 subjects during April 2021. Apo-B and ApoA-I were examined using the Cobas c311/501 instrument with the immunoturbidimetric test method. The results of this study showed a significant relationship between Apo-B levels and BMI, while ApoA-I levels and Apo-B/ApoA-I ratios did not have a significant relationship. In conclusion, there is no relationship between BMI and the ApoB/ApoA-I ratio in male and female subjects.